USING RANDOM TEXT STRATEGYTOWARD STUDENTS’ READING COMPREHENSION AT TENTH GRADE STUDENT OF SMA NEGERI 1 WUNDULAKO - Alifiah Pratiwi; Nur Violeta (Journal of English Education, 2021)
This research aimed at finding out the effects of using random text strategy toward students’ reading comprehension at the tenth grade student of SMA Negeri 1 Wundulako. The problem of this research was “is there any effect of using random text strategy towards students’ reading comprehension at the tenth grade of SMA Negeri 1 Wundulako?”. The objective of this research was to find out the effects of using random text strategy, the data and information about students’ reading comprehension at the tenth grade of SMA Negeri 1 Wundulako. This research was focused on the effect of using random text  strategy towards student’s reading comprehension. The material applied that was narrative text. The design of this reasearch was Quasi – Experimental. The population of this research was the tenth grade students of SMA Negeri 1 Wundulako, and the sample of this research was 25 students of class X.IPS.3 as the experimental class, and 25 students of class X.MIPA.2 as the control class. Based on the result of the research it was find that mean score of post-test 75.028 was higher than pre-test 46.104 and the value of tcount 34.170 was higher than ttable  2.064 at significant level 0,05 and degree freedom =24. It means that H0 was rejected and H1 was accepted. It can be concluding that there was an effects of using random text strategy towards students’ reading comprehension at the tenth grade of SMA Negeri 1 Wundulako.